ChemInform Abstract: Palladium‐Catalyzed, Microwave‐Assisted Synthesis of 3, 4‐Dihydro‐3‐oxo‐2H‐1, 4‐benzoxazines: An Improved Catalytic System and Multicomponent Process. Issue 8 (25th February 2014) - Feng, Gaofeng; Wang, Shengnan; Li, Weiting; Chen, Fengjiang; Qi, Chenze
Abstract An improved catalytic system is developed for the reaction of less reactive aryl chlorides (I) with aromatic amines to produce the title compounds (III).